PERANAN GAMBAR SEBAGAI PAJANAN BAHASA DALAM MEMPERCEPAT PEMEROLEHAN BAHASA ANAK - Ricky Sujana; Ade Kusmana; Eko Kuntarto (Jurnal Komposisi, 2020)
Language is the main means of communication in human life in this world. Language is one of the most important joints in everyone's life. Language can also be learned in certain ways. The learning process can be done by educators through the use of instructional media, one of which is picture media. The role of pictures as a language exposure is a type of language that is not the mother tongue for speakers, but is often used in the environment of the speaker as a medium of continued communication. The purpose of writing this article is to find out the role of images as exposure to language in helping to accelerate children's language. By using the experimental method serves to build relationships that contain causal phenomena which aims to analyze the role of images as language exposure in accelerating the acquisition of children's language. Image media itself at first we recognize the media as a tool in teaching and learning activities that provide visual experiences to children in order to encourage learning motivation, clarify, and facilitate complex and abstract concepts to be simpler, concrete, easy to understand, and accelerate the acquisition children's language. By using pictures as a language exposure makes it more interesting for children to learn languages.